Form and Meaning of Minangkabau Language Reduplication in Solok Selatan District - Syafutri, Husni Dwi; Ahmadi, Alpan (International Journal of Social Sciences and Humanities, 2023)
Language is a tool to communicate in human life and interact appropriately. In addition, in Indonesia, there are also regional languages depending on the regional ethnicity, such as the Minangkabau language. The Minangkabau language has very varied dialects, one of which is the Minangkabau language in the South Solok district. This study discusses Reduplication in the Minangkabau language in the South Solok district. This type of research is qualitative research with a descriptive method. The research data used is linguistic data from secondary and primary sources. The Reduplication discussed it is the form and meaning of Minangkabau language reduplication in the South Solok district. First, the forms of Reduplication found in the Minangkabau language in the Solok Selatan district can be grouped into three, namely (1) forms of noun reduplication, (2) verb reduplication, and (3) adjective reduplication. Second, there are three meanings of Reduplication found in the Minangkabau language in the Solok Selatan district, namely (1) noun reduplication, (2) verb reduplication, and (3) adjective reduplication. There are two forms of Reduplication: (1) root reduplication and (2) affixed basic Reduplication.